Te Hoe Nuku Roa : the long stroke of the paddles that have traversed the globe : a survey on the development of Māori painting from hoe to whare and into the contemporary world : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Creative Arts at Massey University, Palmerston North, Aotearoa, New Zealand - Gibbs, Stephen (Massey University, 2024)
This dissertation, "Te Hoe Nuku Roa: The Long Journey of the Hoe," investigates the whakapapa, visual language, and cultural significance of hoe waka (Māori paddles) traded in 1769, with a primary focus on those with stylistic links to Tūranganui-a-Kiwa. Applying a Whakapapa-a-hoe methodology, developed to activate genealogical links to tīpuna responsible for these taonga, the research complements Kaupapa Māori principles, ensuring Māori conceptual, design, methodological, and interpretive control. Central to this approach is the honouring of Māori values, emphasising whakapapa, Kaupapa Māori principles, and the integration of tikanga-a-iwi. Through extensive museum visits, sensory engagement, creative practice, and design analysis, 23 hoe waka were documented, with 14 traced back to the 1769 exchange off Whareongaonga, south of Te Kuri-Pāoa peninsula. Key findings include the identification of distinctive Tūranganui-a-Kiwa design features, such as the taratara-a-kae surface pattern, and insights into the kōwhaiwhai systems of symmetry. The research also revealed Parkinson’s edits of kōwhaiwhai paintings and the role of Ngāti Rangiwaho as key artists responsible for most of the the hoe waka exchanged on the Endeavour with at least three associated with Rongowhakaata. Contributions to the field include establishing the Whakapapa-a-hoe methodology, expanding knowledge of Tūranganui-a-Kiwa kōwhaiwhai, facilitating the return of taonga, and challenging colonial narratives. The curatorial approach emphasised manaakitanga and whakawhanaungatanga, integrating tikanga-a-iwi into exhibition practices. This study highlights exhibitions such as Toi Tāmanuhiri and Tū Te Whaihanga as platforms for reclaiming mana and promoting Māori voices in museums and academic discourse. This research journey, culminating in this dissertation, has been a deeply personal and transformative experience. Te Hoe Nuku Roa: The Long Journey of the Hoe has explored the whakapapa of hoe waka traded in 1769, the visual language that animates them, and their continuing cultural significance.
Keywords: Toi Māori; Whakairo; Kōwhaiwhai; Hoe; Whakapapa; Tikanga-ā-iwi; Taipūwhenuatanga; Māori Doctoral Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)